Hydrogen sulphide alleviates cadmium stress in Trigonella foenum‐graecum by modulating antioxidant enzymes and polyamine content. (3rd February 2022) - Javad, S.; Shah, A. A.; Ramzan, M.; Sardar, R.; Javed, T.; Al‐Huqail, A. A.; Ali, H. M.; Chaudhry, O.; Yasin, N. A.; Ahmed, S.; Hussain, R. A.; Hussain, I.
ABSTRACT: Cadmium (Cd) toxicity reduces growth and yield of crops grown in metal‐polluted sites. Research was conducted to estimate the potential of hydrogen sulphide (H2 S) to mitigate toxicity caused by Cd in fenugreek seedlings ( Trigonella foenum‐graecum L.). Different concentrations of CdCl2 (Cd1—1 mM, Cd2—1.5 mM, Cd3—2mM) and H2 S (HS1—100 µM, HS2—150 µM, HS3—200 µM) were assessed. Seeds of fenugreek were primed with sodium hydrosulphide (NaHS), as H2 S donor. Seedlings growing in Cd‐spiked media treated with H2 S were harvested after 2 weeks. Cd stress affected growth of fenugreek seedlings. Cd toxicity decreased leaf relative water content (LRWC), intercellular CO2 concentration, net photosynthesis, stomatal conductance and transpiration. However, application of H2 S significantly improved seedling morphological attributes by increasing the activity of antioxidant enzymes, i.e . APX, CAT and SOD, in Cd‐contaminated soil. H2 S treatment also regulated phenolic and flavonoid content. H2 S‐induced biosynthesis of spermidine (Spd) and putrescine (Put) could account for the enhancement of growth and physiological performance of fenugreek seedlings under Cd stress. H2 S treatment also reduced H2 O2 production (38%) and electrolyte leakage (EL, 51%) in seedlings grown in different concentrations of Cd. It is recommended to evaluate the efficacy of H2 S in alleviating Cd toxicity in other crop plants. Abstract : Hydrogen sulphide maintains growth in Trigonella foenum‐graecum exposed to cadmium toxicity by modulating antioxidative defense system and polyamine content.